Baking by flavor - Yockelson, Lisa (New Jersey : Wiley, 2002)
A complete guide to flavor-building ideas that bring out the best in baking Flavor is the very essence of fine baking, the source of wonderful tastes and aromas that tempt the palate and delight the senses. In Baking by Flavor, Lisa Yockelson shares flavor-boosting secrets that can make virtually any recipe burst with new vigor and freshness.
PART I: THE ART OF BAKING BY FLAVOR -- 1. The Way to Bake by Flavor -- 2. An Inventory of Baking Equipment -- 3. Creating a Baking Pantry -- 4. Craft and Technique -- PART II: THE FLAVORS -- 5. Almond -- 6. Apricot -- 7. Banana -- 8. Blueberry -- 9. Butter -- 10. Buttercrunch -- 11. Caramel and Butterscotch -- 12. Chocolate -- 13. Cinnamon -- 14. Coconut -- 15. Coffee and Mocha -- 16. Ginger -- 17. Lemon -- 18. Peanut and Peanut Butter -- 19. Rum -- 20. Spice -- 21. Sweet Cheese -- 22. Vanilla -- 23. About Freezing Baked Goods.
Includes bibliographical references and index.
Keywords: BAKING